Encouraging students to speak in english in an EFL classroom using pop rock songs. - Núñez Sánchez, Yudy Alejandra; Orjuela Cujabán, Diana Katherine; Galvis Molano, Heidy Katherin; Villamizar, Paola; Asesor (Corporación Universitaria Minuto de Dios, 2016)
The aim of this action research was to encourage students to speak in English using pop rock songs. The participants were twenty-one students enrolled in an English II course at Uniminuto. The data was collected from field notes, reflective journals and focus groups during two months. This research is ruled over the following specific fields: Motivation, Speaking, Multiple Intelligences and Multisensory Learning. It was found that students reacted in a positive way towards activities designed using songs. In addition, songs were useful tools to help students to increase their confidence in order to speak with their classmates. In the last chapter of this study, relevant findings, conclusions, implications, limitations and suggestions for further research will be provided.
Keywords: Speak in English; Songs; Multisensory Learning; IDIOMAS EXTRANJEROS; INGLES; MÚSICA EN LA EDUCACIÓN; MÉTODO DE ENSEÑANZA